NakKanak Penter Media: Introducing Numbers and Geometric Shapes to 4-5-Year-Olds - Nurhayati Adhani, Dwi; Nazarullail, Fikri; Latif, Muhammad Abdul; Fitri, Fitri (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
The challenges faced by early-age children in recognizing numbers and geometric shapes in Madura have been a significant concern. This study aims to investigate the NakKanak Penter media in stimulating the recognition of numbers and geometric shapes among 4-5-year-old children. This research falls under the category of Research and Development. The data in this research and development study comprise both qualitative and quantitative data. Qualitative data were gathered through observations, interviews, and documentation. Quantitative data were obtained from research respondents, including subject matter experts, media specialists, cultural experts, and users of educational media. The analysis of this study primarily employs quantitative data analysis. The results of this research indicate that the NakKanak Penter media, which is based on corn as the primary material, aligns with the characteristics of the research location, where corn cultivation is prevalent. This media is deemed suitable for use in introducing numbers and geometric shapes to children. This study contributes by providing the NakKanak Penter media as an alternative medium for early-age children's education in numbers and geometric shapes.